(untitled) (Ius Novum, 2025)
The article analyses the gradually evolving sphere of the metaverse. This sphere is currently, in a sense, a fusion of technological development with the world of the Internet and artificial intelligence, from the perspective of legal considerations crucial to medicine. The article addresses an original issue within the realm of new challenges faced by the law in the era of advancing digitisation. Simultaneously, it has both a review and monographic character. The central thesis posited is that the use of the metaverse in medicine may pose a danger of violating human rights and freedoms, particularly in the areas of individual liberty, personal data protection, and the protection of personal rights, which is relevant from a legal standpoint. The aim of the research conducted was to analyse the application of the metaverse in medicine from a legal perspective and to identify the dangers posed by the metaverse in the context of the risk of infringing fundamental rights and individual freedoms. Additionally, the study aims to propose legislative recommendations in this regard. The subject of the research and its results are original in nature, encompassing not only Polish law but also international law. The application of the research may be significant not only for academia but also for the practice of law, especially in relation to legislative actions at the international, European Union, and national levels.